Optimalisasi Sereh Wangi dan Daun Sirsak sebagai Pestisida Nabati pada Pencegahan Spodoptera litura di Kabupaten Gayo Lues - Arisna Fauzia; Cut Mulyani; Amalia Nazila (Jurnal Surya Masyarakat, 2025)
Cymbopogon nardus and Annona muricata leaf extracts contain active compounds that can be used as botanical pesticides. The use of these botanical pesticides is one step in effective integrated pest management to support sustainable food security. In fact, these plant pests can disrupt the productivity of farmers' and communities' crops. The most common pest that disrupts plant reproduction is the armyworm (Spodoptera litura). This caterpillar, a major enemy, eats many crops, including secondary crops. These crops include vegetables, corn, and so on. There are quite environmentally friendly strategies for controlling armyworms using botanical pesticides. Gayo Lues Regency, which has many types of cultivated plants, often faces problems with this pest. The urgency is because in some areas the use of chemical pesticides on crops in Gayo Lues Regency still uncontrolled. The aims of community service with (KKN) are to create organic farming by utilizing integrated pest management in the form of botanical pesticides as a form of sustainable agriculture. This pesticide was formulated using Cymbopogon nardus mixed Annona muricata leaf leaves. This community service activity was successfully implemented involved the community and village officials. Residents' enthusiasm was also quite high, as evidenced by active participant engagement and discussion sessions. Post-test results also showed an increase the average score for each component, which was 30,10%. Demonstrated of botanical pesticides can accelerate community understanding in the field.